The Eocene-Oligocene boundary climate transition:an Antarctic perspective - Galeotti, Simone; Bijl, Peter K.; Brinkuis, Henk; DeConto, Robert M.; Escutia, Carlota; Florindo, Fabio; Gasson, Edward G. W.; Francis, Jane; Hutchinson, David; Kennedy-Asser, Alan; Lanci, Luca; Sauermilch, Isabel; et al. (Elsevier BV, 2022)
Antarctica underwent a complex evolution over the course of the Cenozoic, which influenced the history of the Earth’s climate system. The Eocene-Oligocene boundary is a divide of this history when the ice-free ‘greenhouse world’ transitioned to the ‘icehouse’ with the glaciation of Antarctica. Prior to this, Antarctica experienced warm climates, peaking during Early Eocene when tropical-like conditions existed at the margins of the continent where geological evidence is present. Climate signals in the geological record show that the climate then cooled, but not enough to allow the existence of significant ice until the latest Eocene. Glacial deposits from several areas around the continental margin indicate that ice was present by the earliest Oligocene. This matches the major oxygen isotope positive shift captured by marine records. On land, vegetation was able to persist, but the thermophylic plants of the Eocene were replaced by shrubby vegetation with the southern beech Nothofagus, mosses and ferns, which survived in tundra-like conditions. Coupled climate–ice sheet modelling indicates that changing levels of atmospheric CO2 controlled Antarctica’s climate and the onset of glaciation. Factors such as mountain uplift, vegetation changes, ocean gateway opening and orbital forcing all played a part in cooling the polar climate, but only when CO2 levels reached critical thresholds was Antarctica tipped into an icy glacial world. CE acknowledges funding by the Spanish Ministry of Economy, Industry and Competitivity (grants CTM2017-89711-C2-1/2-P), cofunded by the European Union through FEDER funds. IS was supported by the Australian Research Council Discovery Project 180102280. A.T. Kennedy Asser was supported by NERC funding (grant no. NE/L002434/1) Edward Gasson is funded by the Royal Society. EG is funded by the Royal Society. AS thanks the European Research Council for Consolidator Grant #771497 (SPANC).